Effect of silane treatments on mechanical performance of kenaf fibre reinforced polymer composites: a review. (9th December 2021) - Nurazzi, N M; Shazleen, S S; Aisyah, H A; Asyraf, M R M; Sabaruddin, F A; Mohidem, N A; Norrrahim, M N F; Kamarudin, S H; Ilyas, R A; Ishak, M R; Abdullah, N; Nor, N M
Abstract: Natural cellulosic fibres, such as kenaf, can be used in polymeric composites in place of synthetic fibres. The rapid depletion of synthetic resources such as petroleum and growing awareness of global environmental problems associated with synthetic products contribute to the acceptance of natural fibres as reinforcing material in polymer composite structures. In Africa and Asia, kenaf is considered a major crop used for various cordage products such as rope, twine, and burlap and in construction, it is used for thermal insulation of walls, floors, and roofs and soundproofing solutions. In the furniture and automotive industry, it is used to manufacture medium-density fibreboard and other composite materials for structural applications. Kenaf is primarily composed of cellulose (approximately 40%–80%), which accounts for its superior mechanical performance. Kenaf fibres are chemically treated before mixing with the polymer matrix to improve their fibre interaction and composite performance. The alkaline treatment with sodium hydroxide (NaOH) solution is the most frequently used chemical treatment, followed by a silane treatment. Numerous chemical concentrations of NaOH and silane solutions are investigated and several combined treatments such as alkaline-silane. The present review discusses the effect of silane treatments on the surface of kenaf fibre on the fabrication of polymer composites and their mechanical properties.